Comparison of Motor Educability Ability of Elementary School Students Based on Gender - Kinanti, Putri Sekar; Samodra, Y. Touvan Juni; Rubiyatno, Rubiyatno (CV Media Inti Teknologi, 2025)
This study aims to determine the comparison of motor educability abilities of elementary school students based on gender. The research method used was a quantitative survey method with a sample of 51 students from grades 1 and 3 at Elementary School 17 Sungai Raya. Data collection was carried out through a test and measurement technique (IOWA Brace Test) which contained 21 test items. The data processing in this study was carried out with the help of excel and SPSS version 26 applications. The results of the study showed that there was a difference in motor educability between boys and girls in terms of age and grade level, this was because male students generally developed motor skills faster and better than female students, who tended to be slower in mastering motor skills. This research has the potential to improve understanding of the differences in motor ability, between boys and girls and provide suggestions for more comprehensive future research.